2005
DOI: 10.1111/j.1467-9450.2005.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Trauma narratives and emotional processing

Abstract: The present study examined the relations between indicators of emotional processing (e.g. trauma narratives), posttraumatic stress symptoms, and psychological distress in two military samples (N = 120) exposed to significant training accidents. Trauma narratives were collected at 2-3 weeks, while outcome measures (e.g. IES-15, PTSS-10, and GHQ-30) were collected at 2-3 weeks, and 4 months after the accidents. Emotional processing was indexed by the content of positive and negative emotional expressions in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
25
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 41 publications
3
25
0
1
Order By: Relevance
“…According to the literature on adults (Brewin & Holmes, 2003;Stein, Trabasso, & Albro, 2001), our data suggest that the narratives of traumatized children are structured on the non-processing of negative emotions: in our study, children with PTSD symptoms reported their traumatic experiences with a greater amount of negative emotions, which are manifested through a wide range of shades (such as anger, sadness, shame, guilt, and disgust; Lee, Scragg, & Turner, 2001), not only with the "standard" PTSD emotions of fear, helplessness, and horror (Grey & Holmes, 2008;Holmes et al, 2005). This result confirms previous studies on adults (Boals & Rubin, 2011;Rubin et al, 2004;Rullkoetter et al, 2009), in which the higher use of negative emotions indicates a more immersion in the traumatic event (Eid, Johnson, & Saus, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…According to the literature on adults (Brewin & Holmes, 2003;Stein, Trabasso, & Albro, 2001), our data suggest that the narratives of traumatized children are structured on the non-processing of negative emotions: in our study, children with PTSD symptoms reported their traumatic experiences with a greater amount of negative emotions, which are manifested through a wide range of shades (such as anger, sadness, shame, guilt, and disgust; Lee, Scragg, & Turner, 2001), not only with the "standard" PTSD emotions of fear, helplessness, and horror (Grey & Holmes, 2008;Holmes et al, 2005). This result confirms previous studies on adults (Boals & Rubin, 2011;Rubin et al, 2004;Rullkoetter et al, 2009), in which the higher use of negative emotions indicates a more immersion in the traumatic event (Eid, Johnson, & Saus, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…Since psychometric properties of the IES-R may differ from one population to another (clinical vs. non-clinical samples), and potentially from one type of threatening situational context to another, the factor structure may differ as a function of the population under study and/or the severity of situational stress experienced. This is particularly relevant when measuring post-traumatic stress symptoms, which, according to previous studies usually develop over time as a function of individual adaptation and processing of traumatic memories (23,24). The sensitivity of the IES is also important when used to detect potential clinical from non-clinical cases.…”
mentioning
confidence: 97%
“…Using the text analysis program Linguistic Inquiry and Word Count (LIWC: (Pennebaker et al, 2007) researchers have found some support for the hypothesis that individuals who produce trauma narratives with proportionally more negative emotional expression and more body state and sensory/perceptual words are more likely to report PTSD symptoms (Alvarez?Conrad, Zoellner, & Foa, 2001; Beaudreau, 2007; Eid, Johnsen, & Saus, 2005; Jones et al, 2007). Overall word use was mixed, with one study finding that participants who used more words in their trauma narratives reported fewer PTSD symptoms (Beaudreau, 2007), and another study finding no association between the number of words used and PTSD symptoms (Alvarez?Conrad et al, 2001).…”
mentioning
confidence: 99%
“…Overall word use was mixed, with one study finding that participants who used more words in their trauma narratives reported fewer PTSD symptoms (Beaudreau, 2007), and another study finding no association between the number of words used and PTSD symptoms (Alvarez?Conrad et al, 2001). One limitation of these existing studies is that most were cross-sectional, and the two that investigated these relationships longitudinally had relatively short follow-up periods of three (Jones et al, 2007) to four months (Eid et al, 2005), making it difficult to discern the temporal relationship between narrative characteristics in trauma narratives and PTSD symptoms.…”
mentioning
confidence: 99%
See 1 more Smart Citation